Auditor switching and investors’ reliance on earnings: Evidence from Bursa Malaysia - Malek, Mazrah; Saidin, Saidatunur Fauzi (David Publishing, 2014)
This study provides some insights of investors’ view on auditor independence focusing on auditor switching. Hence, the purpose of this study is to examine the effect of appointing a new auditor on investors’ reliability on reported earnings in financial accounts.Analyses are based on a matched-pair sample of 162 listed companies in the Bursa Malaysia for the year 2011.The results of the ordinary least squares (OLS) regression show that earnings response coefficients for auditor switching companies are significantly higher than for non-auditor switching companies.The results provide support for the contention that investors place greater reliability on the financial accounts audited by newly appointed auditors.This finding is consistent with the Malaysian audit market where long audit tenure is a common practice and auditor switching is considered rare.Findings provide support for the long discussed issue of the importance of auditor rotation in maintaining auditor independence.